The Influence of Financial Performance on Economic Growth Through The Budget Effectiveness of Regional Government in East Java - Budi Lutfitra Wisada; Erwin Saraswati; Wuryan Andayani (Universitas Airlangga, 2024)
This research aims to empirically test the independent variables Autonomy, Liquidity Ratio and Solvency Ratio which are estimated to influence the dependent variable Economic Growth through the Intervening Variable Budget Effectiveness. The data collection method uses the census method by taking all samples of 228 Regency and City Government Financial Reports throughout East Java Province during the 2017-2022 fiscal year. The data analysis technique used in this research is a quantitative method with the Positivism Paradigm. The analytical methods used in this research are Descriptive Statistics, Classic Assumption Test, Coefficient of Determination Test, Regression Analysis, Hypothesis Testing and Sobel Test using SPSS 27. The research results are show that Autonomy and Liquidity Ratios have a positive and not significant effect on Economic Growth partially. Meanwhile, the Solvency Ratio has a negative and insignificant effect on Economic Growth. Autonomy, Liquidity Ratio and Solvency Ratio have a positive and insignificant effect on Economic Growth through the intervening variable budget effectiveness. The Stewardship Theory, which holds that the regional government will endeavor to serve and perform to the best of its ability for the benefit of the larger community, is supported by this research. This research also contributes to providing input to Regional Heads in East Java to be able to manage finances effectively and efficiently and to be able to produce and manage financial resources and PAD independently by making maximum use of existing resources in the region to increase the production of goods and services. society, GRDP and regional economic growth.